Features of the constitutional and legal regulation of the energy security system of the Republic of Kazakhstan: current state and prospects - Kukeyev, A.K. (Karagandy University of the name of academician E.A. Buketov, 2025)
The article discusses issues related to the definition of mechanisms and legislative provision of energy security. The relevance of the study is due to the emergence of new challenges and threats in this area, which requires timely response and legislative consolidation of the necessary measures. Energy security is an essential aspect of national security, as it directly affects the stability of the State, its economic development and the social well-being of citizens. In the legislation of the Republic of Kazakhstan, the concept of “energy security” is characterized by its versatility and breadth, however, there is no clear definition in regulatory legal acts. In some cases, it is mentioned only descriptively. In turn, the Constitution of the Republic of Kazakhstan, laws and other regulatory legal acts do not provide a sufficiently clear definition of the concept of “energy security”. It is necessary to develop an algorithm of legal argumentation for a clear and precise definition of this term in legislation. This will create a more specific and understandable legal framework for ensuring energy security. As a result, we will be able to better understand what responsibilities the state, private companies and citizens have in protecting energy resources and infrastructure. Since energy security is an integral part of national security, the precise definition of this concept in the legislation of the Republic of Kazakhstan will contribute to strengthening stability in the state. This will allow the government to coordinate its efforts to protect energy resources more effectively and make the country more resilient to external and internal threats.
Қазақстан Республикасының энергетикалық қауіпсіздік жүйесін конституциялық-құқықтық реттеудің ерекшеліктері: қазіргі жағдайы және болашағы
Особенности конституционно-правового регулирования системы энергетической безопасности Республики Казахстан: современное состояние и перспективы
Keywords: energy security; national security; constitutional and legal regulation; energy security system; elements of energy security; energy interests; threats to energy security